Holistic review on the recent development in mathematical modelling and process simulation of hollow fiber membrane contactor for gas separation process - Ng, E.L.H. (Korean Society of Industrial Engineering Chemistry, 2021)
Hollow fiber membrane contactor (HFMC) has been widely studied for gas separation process due to its process intensification capability of combining conventional contactors with membrane technology. In the area of modeling and simulation of HFMC, the development of mathematical model for non-ideal conditions, that is incorporated into process design is key to accurately reflect actual industrial gas separation process. This article aims to review the modelling and simulation techniques, the capabilities and the limitations of different mathematical models in predicting gas separation performance in HFMC for both laboratory analysis and industrial applications. The approach of incorporating the HFMC models into gas separation system and the current progress of process simulation works to develop industrial scale gas separation process will be highlighted. Future works and challenges towards developing comprehensive model in HFMC for industrial gas separation process would also be presented to portray the potential of modelling and simulation in designing and optimizing the HFMC system. Â© 2021 The Korean Society of Industrial and Engineering Chemistry